PENERAPAN BALANCE SCORECARD PADA PERUSAHAAN STARTUP - Sasongko, Agung Hari (Jurnal Ekonomi : Journal of Economic, 2017)
AbstractIn the globalization era, companies based on creative business or Startup have sprung up around the world especially in Indonesia. This is an excellent opportunity. To ensure that the input source used is already effective and efficient in order to achieve company goals, so it is necessary to measure the performance of the company. In sharpening the concept of measurement to be more effective and balance, hence the company needs a method that can measure the performance of corporate strategy appropriately. Balanced scorecard is a performance appraisal by considering four perspectives to measure company performance, which are: financial perspective, customer, internal business process plus learning and growth. Research on the balance of scorecard has been done in various countries. The successful implementation of the balanced scorecard has been proven in many areas. For that purpose, this research will contribute particularly in terms of performance measurement at Startup companies.Keywords : balance scorecard, performance, company